2004
DOI: 10.1023/b:catl.0000038586.24495.95
|View full text |Cite
|
Sign up to set email alerts
|

On the Reactivity of Mo Species for Methane Partial Oxidation on Mo/HMCM-22 Catalysts

Abstract: By characterizing fresh and used Mo/HMCM-22 catalysts with ICP-AES, XRD, NH 3 -TPD technique, UV-Vis DRS and UV Raman spectroscopy, the reactivity of Mo species for methane partial oxidation into formaldehyde were directly studied with a new point of view. By comparing the fresh and used catalysts, it was found that the tetrahedral Mo species bonding chemically to the support surface were practically unchanged after the reaction, while the polymolybdate octahedral Mo species, which had a rather weak interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…In our previous work [22], SbOx/SiO 2 catalysts were prepared from SbCl 3 or SbCl 5 and investigated in methane-selective oxidation to formaldehyde. It was found that the formaldehyde yield obtained on SbOx/SiO 2 catalysts is close to recently reported results [23] for MoOx catalysts. However, little has been known about the speciation of the SbOx species in SbOx/ SiO 2 catalysts other than that the SbOx species can be easily spread on SiO 2 .…”
Section: Introductionsupporting
confidence: 88%
“…In our previous work [22], SbOx/SiO 2 catalysts were prepared from SbCl 3 or SbCl 5 and investigated in methane-selective oxidation to formaldehyde. It was found that the formaldehyde yield obtained on SbOx/SiO 2 catalysts is close to recently reported results [23] for MoOx catalysts. However, little has been known about the speciation of the SbOx species in SbOx/ SiO 2 catalysts other than that the SbOx species can be easily spread on SiO 2 .…”
Section: Introductionsupporting
confidence: 88%
“…05-Reaction Chemistry & Engineering Paper 05058), which partly overlaps with the HZSM-5 intense peak observed at 27.5°. Nevertheless, the absence of a peak at 2θ = 27.3°in the case of Mo-impregnated catalysts points to the much higher degree of Mo dispersal in the zeolite interior or if they are present on the surface, possibly in the form of very small domains (>10 nm) to be detected by a diffractometer, 7,19,32,46 regardless of the impregnation procedure followed for the various Mo precursors. In addition, no peaks associated with the extra-framework molybdate quantities (Al 2 (MoO 4 ) 3 ) were detected in the XRD diffractogram of the as-synthesized catalysts, which may suggest that a small extent of dealumination of zeolitic framework occurs during the Mo incorporation process, 4 which was further corroborated with the 27 Al MAS NMR analysis discussed later.…”
Section: Resultsmentioning
confidence: 99%
“…For Sb 5 [5,9]. It can be seen that the combinational use of antimony and vanadium components evidently enhances formaldehyde yield and the increment of formaldehyde yield, comparing with VO X / This formaldehyde yield obtained on Sb-V-O/SiO 2 catalysts is higher than recent results for single metal oxide catalysts such as molybdenum oxide [15] and vanadium oxide [5,9] catalysts.…”
Section: Methodsmentioning
confidence: 90%
“…Many supported single metal oxide or multi-component metal oxide catalysts have been widely studied in this reaction [4][5][6][7][8][9][10][11][12][13][14][15]. It was found that silica-supported vanadium and molybdenum oxide catalysts were more effective than other catalysts [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation